Metoda vrednotenja arhivskega gradiva na podlagi referenčnih vrednosti - Novak, Miroslav (Moderna arhivistika, 2022)
At the end of 2021 and beginning of 2022, an archival professional question arose at Brezno - Podvelka Elementary School regarding the further storage of e-diaries and e-grade books. In accordance with the existing archival practice in the physical environment, only samples of this documentation should transferred the competent archives. The rest of this documentation should be destroyed by the creator. The established approach objectively represents a long-term risk in the electronic environment, which we define as the systematic establishment of inequality in the use of public archival records. To manage this risk, the authors developed a benchmark appraisal method. The method should be widely applicable for the appraisal of other types of archival records, data, information, contexts, etc. For the purposes of this paper, the authors performed an analysis of the system support and the creation of digital forms of pedagogical documentation. The procedures and the technical environment for the creation of e-diaries and e-grade books at Brezno - Podvelka Elementary School were analysed. At the same time, the current practice of managing e-diaries and e-grade books by the creator and the necessary legislation in the subject area was reviewed. On this basis, an appraisal model was developed together with value scales that take into account reference entities in electronic environments for the purposes of ensuring public trust for these documents. Based on the legally compliant creation of records and their long-term preservation at Brezno - Podvelka Elementary School, the method for the appraisal of electronic archival records was developed. This method takes into account the existing principles and criteria for the appraisal of pedagogical documentation with regards to technical and technological aspects. In this context, the authors point out the importance of reference values of appraisal entities as key to achieving the goals of the comprehensive appraisal in archival theory and practice. With the research, the authors want to encourage a wider archival professional discussion about new approaches and considerations regarding professional activities on digital archival contents. In doing so, archivist must follow several goals, including the provision of public faith not only based on technical, but also from the aspect of contents and references, including needed relations. Brezno - Podvelka Elementary School has adopted internal rules for pedagogical documentation and uses a legally compliant information platform. From this point of view this is an example of good practice in the field of modern records management. E-diaries and e-grade books enable the development and testing of various methods or procedures for managing electronic archival records and other resources both at the creator, as well as at the storage service provider and, last but not least, at the competent archives. All this enables the competent archives not only the testing and developing content appraisal methods, but also other methods and procedures for long-term management of archival entities.
Keywords: appraisal; desing of SIP; e-gradivo; e-records, school documentation, appraisal, sampling, ingest, design of SIP; ingest; oblikovanje SIP; prevzemanje; sampling; school documentation; šolska dokumentacija; vrednotenje; vzorčenje